Automatic lawn mover - Muhammad Muzawir Ahmad Suffi (Department of Electronic Engineering Technology, Faculty of Engineering Technology, University Malaysia Perlis, 2015)
This book represents a survey of the outstanding capabilities of X-ray diffuse scattering for the structural characterization of mesoscopic material systems. The term mesoscopic comprises length scales between a few and some hundreds of nanometers and is of particular importance for low-dimensioal semiconductor nano structures such as quantum dots and quantun wires. In the past decade these objects have attracted huge interest becuase they can be used to create "new" material syatems with altered optical, electronic, and transport properties. In order to acieve this goal, the geometrical parameters of these objects, for example the shape, size, atomistic structure, and strain state have to be well known and controlled through modem fabricationt echnique. Among the most favorable candidates are the " self-organized" growth technique. However, many aspects of the growth mechanisms are still not fully understood. This lead to the necessity to comprehensively study the real structure of mesoscopic systems. Well-adapted characterization technique are required which cover a wide interval of length scales, ranging from the atomic scale up to te micrometer range.